1990
DOI: 10.1111/j.1600-0722.1990.tb00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal microhardness of corroded amalgams: a comparative in vitro study

Abstract: – One conventional and two high‐Cu amalgams were tested for marginal microhardness after 2 months' corrosion in an 85 mM NaCl solution. Amalgams immersed in 200 mM phosphate buffer solution were used as controls. The microhardness tests were conducted on cross‐sections of the amalgams 50μm from the surface edges. The microstructure of the amalgams was studied in SEM and the amounts of Sn, Cu, Zn, Ag, and Hg dissolved in the solutions were analyzed with an atomic absorption spectrophotometer. For the amalgams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
7
1
2
Order By: Relevance
“…In the present study both the marginal microhardness values and the corrosion rates after imtnersion in the test solution were intermediate to those obtained in a previous Table 5 Mean dissolution of elements (\>,gjml) from three amalgams in 85 mM MaCl solution (8). Asterisks indicate statistically higher values compared to mean values of same amalgam in (8) when aqueous solutions of NaCl and phosphate buffer were used separately.…”
Section: Discessioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the present study both the marginal microhardness values and the corrosion rates after imtnersion in the test solution were intermediate to those obtained in a previous Table 5 Mean dissolution of elements (\>,gjml) from three amalgams in 85 mM MaCl solution (8). Asterisks indicate statistically higher values compared to mean values of same amalgam in (8) when aqueous solutions of NaCl and phosphate buffer were used separately.…”
Section: Discessioncontrasting
confidence: 51%
“…This shortcoming ture (5)(6)(7). In a previous study (8), in vitro decreases the life of the restoration and has corrosion and microhardness measurements been related to secondary caries and bulk were used to compare the marginal behavior fractures (4).…”
mentioning
confidence: 99%
“…1975). Patsurakos & Moberg (1988, 1990) have reported that copper release was different in the amalgams with high copper content. In the present study it was determined that the copper release in the low copper‐containing amalgams was higher than that of high copper‐containing amalgams.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the metal release from amalgams can be changed according to the type of test solutions and amalgam type (Patsurakos & Moberg 1988, 1990). Sarkar & Lian (1993) reported that corrosion behaviour changed along with the immersion period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation